STRUKTURALISME DINAMIK DALAM NOVEL A STUDY IN SCARLET KARYA SIR ARTHUR CONAN DOYLE (SUATU KAJIAN KRITIK SASTRA) - Yolanda Naomi Pardede; Syahrul Ramadhan (Indonesian language and literature education program Majapahit Islamic University, 2023)
Literary works are all types of compositions created based on human imagination or imagination and using language as the medium. A good literary work is a literary work that can present a social reality based on heuristic experience and can inspire its audience. A novel is a form of work that contains characters, a series of structured events and can be used as a life experience and provide education to its readers. There are many ways to analyze or study a novel, one of which is dynamic structuralism. This research examines the novel A Study in Scarlet by Sir Arthur Conan Doyle using a dynamic structuralism approach and descriptive qualitative research methods. The data collection techniques used by researchers are observation, reading and note-taking techniques. The data analysis techniques carried out by researchers include data reduction, data presentation, and drawing conclusions. Keywords: dynamic structuralism